Debunking the Western Feminist Framework of the Veiled Woman in Shelina Zahra Janmohamed’s Love in a Headscarf(2010) - Normazla Ahmad Mahir; Zarina Ashikin Zakaria; Mohd Muzhafar Idrus; Norhaili Massari (USIM Press, 2024)
Al-Azkiyaa–International Journal of Language and Education Volume 2, Issue 1 Page (72-83)